The Sharing Economy: A Geographically Weighted Regression Approach to Examine Crime and the Shared Lodging Sector. (September 2019) - Xu, Yu-Hua; Pennington-Gray, Lori; Kim, Jinwon
The sharing economy has gained great market share within the lodging sector by offering cost-effective accommodation solutions. However, it is also troubled by increasing criminal incidents. This study examined the global relationship between the density of Airbnb and crimes in Florida, explored how the relationships vary at the county level. The results suggested that crime-lodging associations vary by listing types but not crime types. Only the Shared Room type consistently exhibited positive associations with both property and violent crimes, while Private Room and Entire Home exhibited negative associations. Local variations were identified by geographically weighted regression, which could be explained by the local tourism development and ethnic diversity degree. We suggested equal efforts in preventing both property and violent crimes in home sharing business. Also regional differences need to be considered when responding to shared lodging crimes.